Seditious Spaces: Protest in Post-Colonial Malaysia - Azlan, Nurul Azreen (A+BE | Architecture and the Built Environment, 2018)
The title ‘Seditious Spaces’ is derived from one aspect of Britain’s colonial legacy in Malaysia (formerly Malaya): the Sedition Act 1948. While colonial rule may seem like it was a long time ago, Malaysia has only been independent for sixty-one years, after 446 years of colonial rule. The things that we take for granted today, such as democracy and all the rights it implies, are some of the more ironic legacies of colonialism that some societies, such as Malaysia, have had to figure out after centuries of subjugation. While not suggesting that post-colonial regimes should not be held accountable for their actions, it is ironic to see a BBC commentator grilling the leader of a Commonwealth state about repressive laws and regulations inherited from the colonial era. (Even the term ‘Commonwealth’ is itself ironic, implying shared wealth, in reality it commonly meant a colonised country was contributing to the wealth of the metropolitan centre). This research sought to understand how the trajectory of urban development, which is shaped by the colonial legacy, has produced the contemporary geography of contention in Malaysia. Given that public space is shaped by the colonial legacy, how does it facilitate or hinder street protests as a function of democracy, which is also a vestige of colonialism? To do this, rather than going into a long discussion about notions of public sphere and public space, much of which originated from Western traditions, I used postcoloniality as a lens for the topic1. By taking the concepts as a given, the postcolonial gaze allowed me to contextualise particular Malaysian conditions. In this thesis I argued that the postcolonial narrative (democracy, modernisation, development) is ambivalent precisely because the colonial narrative itself is ambivalent; there was no real break between colonisation and the present condition. I examined three aspects in particular. Firstly, colonial architecture as a subversive ‘third space’, where independence amplified the subversive quality of colonial architecture because of the power vacuum left after the colonisers had left. Secondly, postcolonial ‘amnesia’, where certain aspects of history were conveniently forgotten or others selectively remembered in the production of space to build a hegemonic vision of society. Finally, I looked at postcolonial mimicry, where the post-colonial society imitated either the former colonial master or some other references that fit within its narrative. These notions were mapped onto public space which not only provided the backdrop for dissent but also shaped its form and practices. Protest provided a direct line for the interrogation of just how democratic postcolonial public space actually is. The mobilisations, negotiations, and potential conflicts that arise from the moment a street protest is announced reveal a lot about the politics of space as much as the event itself. Public space comprises material and discursive spaces and, at the time of writing, included social media which has become part of the infrastructure of protest. The empirical part of this research came from the Bersih 4 protest in Kuala Lumpur, which took place from 29-30 August 2015. To ground the somewhat abstract postcolonial discussion, methods (outlined below) were used to collect and analyse data. Firstly, to understand the logic behind the control and surveillance of public space I reviewed literature on how architecture and public space are produced and governed in Malaysia. Secondly, I observed protest in both digital and material public space, which means I harvested social-media data about the protest but also observed street protests in Kuala Lumpur. This informed me how protest produces space within which protesters could foster a collective identity, something that is necessary for the continuity of the protest. I then conducted a thematic analysis on a large number of tweets collected during the protest to understand how information about their places were communicated. Other protests that have taken place in Kuala Lumpur since 1998, when new media started playing a role, were also mapped; this was crucial for the understanding of the spatial patterns of the protests. By tracing the production of architecture in Malaysia we can see how the nation-building project was an ambivalent one, evidenced by how the state mapped their aspirations onto the built environment. Postcolonial amnesia is exhibited in how the Malay-Muslim identity is amplified in architecture while other identities were suppressed and only utilised when it seemed productive. Mimicry, on the other hand, can be seen in how certain architecture is created based on an imagined past, and how visions of modernity fluctuate between Occidental and Orientalist visual cues. Malaysian public space is not only a colonial legacy in terms of its material infrastructure and regulations, it also carries traces of colonial practice. Here, mimicry was manifested in how society imitated the erstwhile colonial masters in seeking to avoid the Other (due to the perception that public space is dangerous and uncomfortable, and showing that segregation had moved from one defined by ethnicity to one defined by class). The lack of a clear break between the colonial and the Neoliberal can also be seen in how public space is governed. Undesirable activity was always framed according to its potential for disrupting economic activity, indicating that public space was perceived as being useful only for production and consumption, not for the performance of citizenship. An urban-planning assessment of Kuala Lumpur and Putrajaya (the seat of the postcolonial government) was carried out to see which place could better support protest. Accessibility, land-use patterns, and urban form were all aspects of the city that were decided upon at the urban-planning level and throught to influence the probability of protest taking place. This indicates that a city can be designed to support or hinder the performance of democracy. I found that Kuala Lumpur, founded during the colonial era, was actually more supportive of protest activities than Putrajaya, a city purpose built by the newly independent democratic regime. Analysis based on data collected around Bersih 4 was organised into four themes. I first examined how protest produces space. I did this by tracing how the collective identity, already formed by previous Bersih protests, was cultivated on social media in order to mobilise protesters to take to the streets. The act of converging in the same space and performing these spatial choreographies (marching, knowledge-sharing, occupation) further enhanced the collective identity. Images and descriptions of what took place on the streets then travelled through social media which in turn propelled events in the public space. While protest is shaped by the materiality of the urban environment, protest also produces space. Secondly, a reading of the space revealed the interplay between symbolic places and the spaces of everyday life. Protests are shaped by the existing materiality of space, which the authorities could further control by putting up extra measures. Due to this, Bersih 4 ended up occupying the intersection between symbolic and institutional places and spaces of everyday life. The polite restraint shown by Bersih 4 (in not entering Dataran Merdeka – which was barred to them) served to amplify the distance between the state and the people, further magnified by the fact that the protest coincided with Independence Day (31 August). The junction that Bersih occupied was teeming with people throughout the occupation but Dataran Merdeka was left empty and silent on the eve of the Independence Day commemoration. On the other hand, a thematic analysis of tweets revealed that most of those that mentioned geographical places were inflammatory in nature, in the sense that they were urging people to join the protest. Therefore, while the state could construct the symbolism of the space, it does not mean that the space is viewed in a similar way by the people, which means, in turn, that it can be rewritten. This is one way in which the subversiveness of colonial architecture was manifested. Thirdly, I found that the control of digital and material space was symmetrical. This can be seen in three ways: One, how regulations of both spaces can be used to suppress dissent; Two, how access to space can be blocked, either by blocking certain websites or platforms, or by limiting the access to the material public space; and Three, bottom‑up disruptions – while the Red Shirts disrupted Bersih’s performativity in the material public space, cybertroopers were disrupting protest exchanges on Twitter. Finally, the digital and spatial divide between Bersih and its opponents. The digital divide was not defined by degrees of expertise, but, rather, it revealed a differing logic of operation based on norms shaped by what was available to these different parties. Geographically, it revealed the difference between experience of organising protests for a collective cause versus a lack of experience (compounded by racist motivations). What this indicated was that the cleavage does not only run along communal lines, is also political. The research showed how the production of the Malaysian built environment is ambivalent, as is evidenced by the traces of amnesia and mimicry found in the narrative, where identities are grafted onto projections of modernity. Putrajaya shows that there is a disconnect between what the regime claims itself to be, a democracy, and the city it builds. What Putrajaya seems to demonstrate (ironically, as the seat of a democratic government) is how urban planning can be used to design a city so that it does not support the performance of democracy. It is also ironic how Kuala Lumpur, a city founded during the colonial period, is now more accommodating to street protest, cementing its position as a subversive third space. The disconnect between the ideology of the regime and the kind of space it produces indicates a potential for architects and urban planners to be subversive by designing public space to be more democratic, regardless of a regime’s ideology. Kuala Lumpur’s mixed land-use patterns, accessible by multi-modal transportation and a tight urban form which gives the city a more walkable scale, indicates that the city is a place of everyday life since it supports a variety of functions and activities within easy reach of the populace. Since protests also seem to flourish in public spaces like these, where everyday life is lived, it further cements the role of protest as a part of public life. The research also indicated the necessity of having material public space for the performance of democracy, thereby debunking the myth that digital space has somehow superseded public space. Just as the assumption that the Internet would result in the death of distance (ease of communication has, ironically, led to global cities becoming ever more important as nodes in global networks), this research shows how the Internet has the potential to expand the public sphere, and is actually instrumental in getting people to physically go to public spaces. Given how the protesters were communicating about place during Bersih 4, it shows how contestation of meaning does not have to be direct clash but that digital space could provide an arena even when material public space is off limits. The way in which Bersih 4 materialised itself in Kuala Lumpur also shows that restraint on the part of the protesters could also be a productive protest strategy, since it can bridge the distance between the state and its citizens via a strategic reading (and occupation of) space. Since protest is a performance, in the sense that it is a way of communicating displeasure, the space it uses should not only be seen as something to use or overcome, but can also be utilised more actively. Bersih 4, through its occupation of an important street junction, showed how it could challenge the symbolism embedded within Dataran by amplifying it. This research also shows how access to public space is crucial for the performance of democracy, and how public space can actually be designed to be more democratic, regardless of the ideology of the regime. Democracy has a spatial quality, and design can play a role in fomenting a more democratic urban environment.